(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. La Direttiva 2000/78 CE e i casi Egenberger e IR arrivati a Lussemburgo - 3. Autonomia delle chiese e tutela giurisdizionale dei diritti all’interno delle organizzazioni religiosamente orientate. I contenuti criptici delle pronunce di Lussemburgo - 4. Il requisito ideologico nelle organizzazioni di tendenza. Le integrazioni della Corte UE e le riletture in corso da parte confessionale - 5. L’art. 17 TFUE e l’attesa di chiarimenti. Religious-Ethos Employers between European Directive, national laws and Court of Justice EU ABSTRACT: This article examines two recent rulings of the Court of Justice of the European Union (cases Egenberger and IR). These are the first rulings on art. 4, par. 2, Directive 2000/78/EC on “occupational activities within churches and other public or private organisations the ethos of which is based on religion or belief“. On the one hand the author focuses on the passages concerning religious autonomy and jurisdictional protection of rights; on the other hand she highlights the links between the jurisprudence of the two European courts (CJEU and ECHR) and tries to reconcile the statements of the Court of Justice and those of the German constitutional Court on the limits to the autonomy of churches. However, the article highlights how the Court of Justice has not adequately addressed neither the art. 10 of the European Charter of Fundamental Rights EU, nor the art. 17 of the TFEU. As regards the ideological requirement set by art. 4, par. 2 of the European Directive, the study focuses on the additions made by the Court of Justice and recalls the reinterpretations of the ideological requirement recently adopted by the Catholic and Evangelical Churches in Germany.